“Clown Children” Quo Vadis Guarantee Education for Children with Special Needs in the Era of Covid-19 - Khamim Zarkasih Putro; Muhammad Shaleh Assingkily; Angga Febiyanto; Zaini Dahlan (AL-ISHLAH: Jurnal Pendidikan, 2021)
This paper aims to analyze education guarantees for children with special needs (ABK) in the Covid-19 era. The focus of the study is the phenomenon of crew members clowning on the streets of Medan City. The theory used in analyzing the data is the theory of implementation of Merilee S. Grindle's policies. This research uses a qualitative approach with a case study method. Data was collected using an open interview technique, participant observation, and documentation study. Furthermore, the data were analyzed through data reduction techniques, data display, and concluding. This study indicates that the North Sumatra government has been very responsive to inclusive education for children with special needs in the region.This is indicated by two things, namely (1) the declaration of North Sumatra as the Province of Inclusive Education since 2015 and (2) the issuance of the Governor of North Sumatra No. 29 of 2016 concerning the Implementation of Inclusive Education as a follow-up to Permendiknas Number 70 of 2009.